Active displacement control of pantograph-catenary system for a half-body railway model - Abdullah, Mohd Azman; Harun, Mohd Hanif; Ahmad, Fauzi; Ibrahim, Munaliza; Mohamed Jamil, Fathiah (Budapest University of Technology and Economics, 2024)
The pantograph is an essential component that provides electrical contact between the overhead wires and the electric train. The quality of the current collection in high-speed trains is directly influenced by the mechanical interaction between the pantograph collector head and the overhead contact line. To overcome these challenges and improve pantograph performance, researchers and engineers have explored innovative solutions, including the introduction of active control mechanisms. Excitation by the vehicle is one of the normal disturbances in the dynamic interaction of the pantograph and the overhead line. The vertical effects of vehicle-track vibrations on the interaction between the pantograph and the overhead contact line have not yet been adequately researched. To fill this research gap, this study establishes models for both the pantograph-catenary interaction and the vehicle-track system. In this study, the performance of the modified Skyhook-Proportional-Integral-Derivative (PID) controller was investigated for a half-body of a railway pantograph-catenary system. Track irregularities such as step, sine, and random were applied to perturb the suspension system. The performance of both passive and active systems was investigated by considering the track irregularities as a basis. The root mean square analysis (RMS) found that active displacement control of pantograph-catenary systems for a half-body railway model equipped with modified Skyhook-PID controllers performed better than the passive systems. In summary, the future experimental approach for active half-body railway model could incorporate this simple modification of the Skyhook-PID controller.